MEMBANGUN PERILAKU KERJA RAMAH LINGKUNGAN PADA PEGAWAI PEMERINTAHAN DI KABUPATEN BENGKALIS, RIAU - Rosa, Nageeta Tara (Jurnal Administrasi Profesional, 2025)
Abstract Establishing an environmentally friendly behavior contributes to environmental awareness by integrating environment practices into daily employee activities at their workplace due to most of its time is at work, and it refers to motive that workplace that had environmentally friendly work behavior bring the employees working in a supportive work environment and may perceive more motivates to deliver high quality work consistently and bring them to the employee well-being, reduces operational of Government Agencies’ costs, and positively impacts the environment. This exploratory qualitative research comprised the Respondents from six government employees or the State Civil Apparatus (ASN) who served in 3 (three) of government agencies including the horticulture, environment, and healthcare in one district/city in Bengkalis Riau Province. The findings of this research encompass five factors that can support in establishing an environmentally friendly behavior in government agencies. First, compiling and practicing policy instrument on environmentally friendly work behaviour in government areas. Second, enhancing the leadership's charge and role-modeling for being environmentally friendly behavior. Third, practicing and executing diverse environmentally friendly plan either solution and relating it into State Civil Apparatus. Fourth, adopt the technology that support environmentally friendly offices, and lastly, conduct training (education) and socialization on an environmentally friendly behavior to State Civil Apparatus. Hence those efforts affected the better human activities in the workplace. Keywords: Work Behavior, Environmentally Friendly, Government Agencies, Employee Well-Being